1995
DOI: 10.1111/j.1476-5381.1995.tb15898.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of adrenomedullin‐induced renal vasodilatation by NG‐nitro L‐arginine but not glibenclamide

Abstract: 1 The present study was conducted in order to elucidate the in vivo contribution of nitric oxide (NO) and the glibenclamide-sensitive potassium channel in the renal action of adrenomedullin in anaesthetized dogs. 2 Intrarenal arterial infusion of adrenomedullin (20 ng kg' min-) elicited a pronounced increase in renal blood flow with no changes in systemic blood pressure. The renal vasodilator action of adrenomedullin was markedly attenuated by pretreatment with N0-nitro L-arginine (L-NOARG), but this was rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 24 publications
0
45
1
1
Order By: Relevance
“…The peptide has been demonstrated in the endothelial cells of human cavernosal tissue (Marinoni et al, 2005). Adrenomedullin inhibits the contraction of several types of smooth muscle cells not only through an increase in cAMP production, but also be stimulating the release of NO (Miura et al, 1995). Injected intracavernosally in cats, adrenomedullin caused increases in intracavernosal pressure and in penile length, an effect also found with CGRP (Champion et al, 1997a,b,c).…”
Section: Adrenomedullin Calcitonin Gene-related Peptidementioning
confidence: 79%
“…The peptide has been demonstrated in the endothelial cells of human cavernosal tissue (Marinoni et al, 2005). Adrenomedullin inhibits the contraction of several types of smooth muscle cells not only through an increase in cAMP production, but also be stimulating the release of NO (Miura et al, 1995). Injected intracavernosally in cats, adrenomedullin caused increases in intracavernosal pressure and in penile length, an effect also found with CGRP (Champion et al, 1997a,b,c).…”
Section: Adrenomedullin Calcitonin Gene-related Peptidementioning
confidence: 79%
“…26 Although the exact mechanisms by which AM produces vasodilatation are not defined, there is evidence that it acts indirectly through NO and through cAMP-mediated mechanisms and via the inhibition of angiotensin II and endothelin production. 20,[32][33][34] AM in animals also acts in the kidney, relaxing both efferent and afferent glomerular arterioles, increasing glomerular filtration, and inducing natriuresis. 32,33 In addition, AM may inhibit VSMC and cardiac muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, long-term AM infusion significantly decreased the plasma renin concentration in DS rats. In previous studies, the effects of acute administration of AM on plasma renin activity in vivo were controversial, 20,21 because excessive reduction of blood pressure induced by AM may induce renin secretion. However, Khan et al 17 reported that chronic administration of AM significantly reduced the plasma renin activity in renovascular hypertensive rats, suggesting direct inhibitory effects of chronic AM infusion on renin secretion.…”
Section: Discussionmentioning
confidence: 99%